Spatial-Sequential Working Memory in Younger and Older Adults: Age Predicts Backward Recall Performance within Both Age Groups - Brown, Louise A. (Frontiers in Psychology, 2016)
Working memory is vulnerable to age-related decline, but there is debate regarding the age-sensitivity of different forms of spatial-sequential working memory task, depending on their passive or active nature. The functional architecture of spatial working memory was therefore explored in younger (18-40 years) and older (64-85 years) adults, using passive and active recall tasks. Spatial working memory was assessed using a modified version of the Spatial Span subtest of the Wechsler Memory Scale – Third Edition (WMS-III; Wechsler, 1998). Across both age groups, the effects of interference (control, visual, or spatial), and recall type (forward and backward), were investigated. There was a clear effect of age group, with younger adults demonstrating a larger spatial working memory capacity than the older adults overall. There was also a specific effect of interference, with the spatial interference task (spatial tapping) reliably reducing performance relative to both the control and visual interference (dynamic visual noise) conditions in both age groups and both recall types. This suggests that younger and older adults have similar dependence upon active spatial rehearsal, and that both forward and backward recall require this processing capacity. Linear regression analyses were then carried out within each age group, to assess the predictors of performance in each recall format (forward and backward). Specifically the backward recall task was significantly predicted by age, within both the younger and older adult groups. This finding supports previous literature showing lifespan linear declines in spatial-sequential working memory, and in working memory tasks from other domains, but contrasts with previous evidence that backward spatial span is no more sensitive to aging than forward span. The study suggests that backward spatial span is indeed more processing-intensive than forward span, even when both tasks include a retention period, and that age predicts backward spatial span performance across the adult lifespan, within both younger and older adulthood.